Bioactivity in an Aggrecan 32‐mer Fragment Is Mediated via Toll‐like Receptor 2. Issue 5 (May 2015) - Lees, Sophie; Golub, Suzanne B.; Last, Karena; Zeng, Weiguang; Jackson, David C.; Sutton, Philip; Fosang, Amanda J.
<x xml:space="preserve">Abstract</x> Objective To determine whether an aggrecan 32‐mer fragment derived from dual ADAMTS and matrix metalloproteinase (MMP) cleavage in the aggrecan interglobular domain was bioactive and, if so, to elucidate its mechanism of action. Methods Mouse primary chondrocytes, synovial fibroblasts, or peritoneal macrophages, human primary chondrocytes, and cells or cell lines from myeloid differentiation factor 88 (MyD88)–deficient and Toll‐like receptor 2 (TLR‐2)–deficient mice were stimulated with synthetic mouse 32‐mer peptide, human 32‐mer peptide, a 32‐mer scrambled peptide, or native, glycosylated 32‐mer peptide. Cells stimulated with 32‐mer peptide were analyzed for changes in messenger RNA (mRNA) expression by quantitative polymerase chain reaction. Conditioned medium was analyzed for levels of interleukin‐6 protein by an AlphaLISA or for levels of MMP‐3 and MMP‐13 protein by Western blotting. NF‐κB activation was measured in a luciferase reporter assay. Results Treatment of mouse cells or cartilage explants with 32‐mer peptide or scrambled peptide revealed that the 32‐mer peptide, but not the scrambled peptide, had antianabolic, procatabolic, and proinflammatory bioactivity in vitro. Chondrocytes, synovial fibroblasts, and macrophages from MyD88‐deficient mice failed to respond to 32‐mer peptide stimulation. A macrophage cell line derived from TLR‐2–deficient mice also failed to respond to 32‐mer peptide stimulation. Stimulation of human chondrocytes with human 32‐mer peptide increased the expression of catabolic markers at the mRNA and protein levels. Mouse and human 32‐mer peptide stimulated NF‐κB activation in a TLR‐2–dependent reporter assay, and the response of chondrocytes from both species to native, glycosylated 32‐mer peptide was similar to the response to synthetic peptides. Conclusion The aggrecan 32‐mer fragment is a novel endogenous ligand of TLR‐2 with the potential to accelerate cartilage destruction in vivo.